3(-4-2c)=-24

Simple and best practice solution for 3(-4-2c)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-4-2c)=-24 equation:



3(-4-2c)=-24
We move all terms to the left:
3(-4-2c)-(-24)=0
We add all the numbers together, and all the variables
3(-2c-4)-(-24)=0
We add all the numbers together, and all the variables
3(-2c-4)+24=0
We multiply parentheses
-6c-12+24=0
We add all the numbers together, and all the variables
-6c+12=0
We move all terms containing c to the left, all other terms to the right
-6c=-12
c=-12/-6
c=+2

See similar equations:

| x=-7/5-70 | | (3x−5)=−8 | | 34=–2(4–3x) | | 6−2(3x−5)=−8 | | 9X-8=4+8x | | 14.75+0.12(x+3)=15.25+0.11x | | 20x+x^2=-25 | | 9=2/5m | | k8+7=18 | | -2=2÷(p+-18) | | -52=12m-10+m | | Y-0.25x=-1 | | 25×2^x=25600 | | 120÷f=1.2 | | 6(f-4)=6 | | 3x-4=7×+12 | | 1525=-15x+400 | | 5(x+1=-5 | | 6+-2x=11 | | 4x+4=2x+34 | | (-18+p)÷2=-2 | | 9)10=4-y | | (x+1)x6=36 | | 16x+9-2x=9 | | -4j=-2j+10 | | 300-10x=410 | | I3(x-4)I+7=16 | | 4+0.09x=10 | | s*7+22=169 | | 5(3z-3=30 | | 192=0.09x+12 | | 3x+34=9 |

Equations solver categories